The role of isolators in two-phase kerosene/air rotating detonation engines - Wenbo Cao; Fang Wang; Chunsheng Weng; Huangwei Zhang (Defence Technology, 2025)
In this study, the three-dimensional non-premixed two-phase kerosene/air rotating detonation engines with different isolator configurations and throat area ratios are simulated by the Eulerian-Lagrangian method. The effects of the divergence, straight, and convergence isolators on the rotating detonation wave dynamics and the upstream oblique shock wave propagation mechanism are analyzed. The differences in the rotating detonation wave behaviors between ground and flight operations are clarified. The results indicate that the propagation regimes of the upstream oblique shock wave depend on the isolator configurations and operation conditions. With a divergence isolator, the airflow is accelerated throughout the isolator and divergence section, leading to a maximum Mach number (∼1.8) before the normal shock. The total pressure loss reaches the largest, and the detonation pressure drops. The upstream oblique shock wave can be suppressed within the divergence section with the divergence isolator. However, for the straight and convergence isolators, the airflow in the isolator with a larger ψ1 (0.3 and 0.4) can suffer from the disturbance of the upstream oblique shock wave. The critical incident angle is around 39° at ground operation conditions. The upstream oblique shock wave tends to be suppressed when the engine operates under flight operation conditions. The critical pressure ratio βcr0 is found to be able to help in distinguishing the propagation regimes of the upstream oblique shock wave. Slightly below or above the βcr0 can obtain different marginal propagation results. The high-speed airflow in the divergence section affects the fuel droplet penetration distance, which deteriorates the reactant mixing and the detonation area. Significant detonation velocity deficits are observed and the maximum velocity deficit reaches 26%. The results indicate the engine channel design should adopt different isolator configurations based on the purpose of total pressure loss or disturbance suppression. This study can provide useful guidance for the channel design of a more complete two-phase rotating detonation engine.